Targeting the NMDA receptor/NO signalling pathway following L-α aminoadipic acid-induced astrocytic impairment and associated changes in the structural plasticity of neurons - DAVID, JENNIFER (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2018)
This investigation firstly aims to characterise the impact of astrocytic dysfunction on neurons in vitro, specifically the effects of L-α amino adipic acid (L-AAA)-induced astrocytic dysfunction on neurite outgrowth and synapse number in primary cortical neurons. Treatment with conditioned media (CM) derived from healthy astrocytes increased neurite outgrowth in immature neurons and synapse number in mature neurons. In contrast, CM derived from L-AAA-treated astrocytes impaired neurite outgrowth in immature neurons and reduced spine density and synapse formation in mature neurons. In addition, L-AAA provoked a reduction in the astrocytic markers glial fibrillary acid protein (GFAP) and the glutamate aspartate transporter (GLAST) and resulted in altered mitochondrial respiration in astrocytes. The second part of this project focused on the translation from in vitro experiments to an animal model of L-AAA-induced astrocytic dysfunction. Testing L-AAA-induced astrocytic dysfunction in mice serves to scale this work by assessing the effect of astrocytic dysfunction on behaviour, neuronal complexity and dendritic spine density in the prelimbic cortex (PLC) in vivo. Following L-AAA delivery to the PLC, transient depressive-like behaviour in the forced swim test (FST) and reduced GFAP immunoreactivity in the PLC were evident over a 72h post-administration period leading to a full recovery over 7 days. Moreover, L-AAA decreased dendritic spines of mushroom variety 72h after administration with no effect on the number of primary neurites in the PLC. Finally the effect of targeting the neuronal NMDA-R/NO signalling pathway is assessed as a strategy to prevent neuronal atrophic effects following L-AAA-induced astrocytic dysfunction. Co-treatment of neurons with the NMDA-R antagonist ketamine, as well as the nNOS inhibitor TRIM and the PSD-95/nNOS inhibitors IC87201 and ZL006 partially protected against reduced neurite outgrowth and synapse formation induced by CM from L-AAA treated astrocytes. In mice, results demonstrate that the PSD-95/nNOS inhibitor (ZL006) had no effect on dendritic spine density or the number of primary neurites. In vivo, exposure to the FST reduced spine density. ZL006 was able to attenuate FST-induced decreased spine density 24h after administration. ZL006 and TRIM were also able to block depressive-like behaviour observed in the FST. Interestingly, FST combined with L-AAA drove the changes in the opposite direction and increased dendritic spine density. ZL006 response reduced spine density and produced an antidepressant-related response in the FST following L-AAA administration. The results highlight the importance of astrocytes, in particular the consequences of astrocytic impairment on neuronal complexity and synapse formation, and support the hypothesis that selectively targeting the PSD-95/nNOS interaction downstream of the NMDA-R prevents neuronal atrophic effects and potential synapse loss.
APPROVED
Keywords: Astrocytes, NMDA-R, Nitric oxide, depression